1997
DOI: 10.3109/01674829709080702
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure issues and decisions of couples who conceived via donor insemination

Abstract: Disclosing the use of donor insemination (DI) to family, friends, and offspring poses a quandary for many DI patients. A cross-sectional survey was conducted to determine whether couples opted to share information about conception via donor sperm with their children, as well as the issues and concerns that arose for parents once infertility treatment was completed. Twenty-seven married heterosexual infertile husbands and wives who had used DI to conceive completed a follow-up questionnaire asking them about di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 19 publications
2
23
2
2
Order By: Relevance
“…Even in Sweden, where legislation giving donor offspring the right to obtain information about the donors' identity came into force in 1985, more than a decade later, only 11% of parents had informed their children of their donor conception . Investigations in the United States have produced comparable findings, with rates of disclosure to the children reported to range between 14% and 30% (Leiblum & Aviv, 1997;Nachtigall, Tschann, Szkupinski Quiroga, Pitcher, & Becker, 1997). When questioned about their reasons for secrecy, parents in the European Study of Assisted Reproduction Families reported concern that their children would be upset, shocked, and confused by the knowledge that their fathers or mothers were not genetically related to them (Cook, Golombok, Bish, & Murray,1995;Golombok et al, 1999).…”
Section: Rates Of Disclosure In Donor-conceived Familiesmentioning
confidence: 98%
“…Even in Sweden, where legislation giving donor offspring the right to obtain information about the donors' identity came into force in 1985, more than a decade later, only 11% of parents had informed their children of their donor conception . Investigations in the United States have produced comparable findings, with rates of disclosure to the children reported to range between 14% and 30% (Leiblum & Aviv, 1997;Nachtigall, Tschann, Szkupinski Quiroga, Pitcher, & Becker, 1997). When questioned about their reasons for secrecy, parents in the European Study of Assisted Reproduction Families reported concern that their children would be upset, shocked, and confused by the knowledge that their fathers or mothers were not genetically related to them (Cook, Golombok, Bish, & Murray,1995;Golombok et al, 1999).…”
Section: Rates Of Disclosure In Donor-conceived Familiesmentioning
confidence: 98%
“…In contrast to the majority attitude of heterosexual couples who favor not disclosing their conception by means of gamete donation to their children (Leiblum and Aviv 1997;Salter-Ling et al 2001;Scheib et al 2003;Lycett et al 2005;Burr and Reynolds 2008;Freeman et al 2009;Jadva et al 2009;Blake et al 2016), single mothers and lesbian couples, whose families differ from conventional families in that 'there is no father', particularly favor disclosing how they have been conceived to their children (Leiblum et al 1995;Brewaeys 2001;Vanfraussen et al 2001;Murray and Golombok 2005;Freeman et al 2009;Landau and Weissenberg 2010;Gross 2014 ).…”
Section: Isabel Jociles Ana M Rivas and Consuelo áLvarez Introdumentioning
confidence: 88%
“…Furthermore, there is no evidence from studies conducted with parents of donor-conceived children that the removal of anonymity would make it any less likely that parents would tell their children of the circumstances of their conception. Research conducted before removal of anonymity suggests that most children are ignorant of their donor offspring status [22][23][24][25]. Other European studies revealed that most couples did not intend to tell their children of their DI origins [26][27][28].…”
Section: Rights Of the Childmentioning
confidence: 99%
“…More recently, Golombok et al [25], in a study of 94 families with children conceived by DI, found that only 8.6% of DI children had been informed about their genetic origins, compared with 50% of in vitro fertilization (IVF) parents and 95% of adoptive parents. At most, only basic donor information was deemed important (for example, ethnicity, hight, education and health information) [24,29].…”
Section: Rights Of the Childmentioning
confidence: 99%